The relationship between acoustic and musical pitch processing in adolescents. Issue 4 (4th April 2022) - Zendel, Benjamin Rich; Demirkaplan, Özgen; Mignault‐Goulet, Geneviève; Peretz, Isabelle
Abstract: Amusia is defined as a difficulty processing the tonal pitch structure of music such that an individual cannot tell the difference between notes that are in‐key and out‐of‐key. A fine‐grained pitch discrimination deficit is often observed in people with amusia. It is possible that an intervention, early in development, could mitigate amusia; however, one challenge identifying amusia early in development is that identifying in‐ and out‐of‐key notes is a metacognitive task. Given the common co‐occurrence of difficulties with pitch discrimination, it would be easier to identify amusia in developing children by using a pitch change detection task. The goal of this study was to explore the behavioural and neurophysiological profiles of adolescents with poor pitch processing (Poor PP) abilities compared with those with normal pitch processing (Normal PP) abilities. Neurophysiologically, the Poor PPs exhibited a similar event‐related potential (ERP) profile to adult amusics during both acoustic and musical pitch discrimination tasks. That is, early ERPs (ERAN, MMN) were similar in Poor PPs compared with Normal PPs, whereas late positivities (P300, P600) were absent in Poor PPs, but present in Normal PPs. At the same time, behavioural data revealed a double dissociation between the abilities to detect a pitch deviant in acoustic and musical context, suggesting that about a third of the children would be missed by selecting a fine‐grained acoustic pitch discrimination task to identify the presence of amusia in early childhood. Abstract : Amusia is associated with deficits in both acoustic and musical pitch discrimination. Early identification of amusia could lead to improved treatment possibilities. Here, we demonstrate that there is a double dissociation between abnormal acoustic pitch discrimination and abnormal musical pitch discrimination in adolescents. These results suggest that acoustic pitch discrimination should not be used in isolation to identify cases of amusia in children.